Understanding organizational culture and learning processes to the success of the knowledge management (Perspectivas em Ciência da Informação, 2009)
Although companies have been trying to enlarge their organizational knowledge in order to obtain competitive advantages, the knowledge management has found opposition, for it is impossible not to work the culture of organizations and their learning processes if there is a real interest in managing knowledge. Depending on the type of the predominant culture and the opening that is given to organizational learning, a company can open or close itself to the process of learning management. So, this article raises the necessity of giving attention to the organizational culture and to its processes of learning so that the knowledge management can be successful. Organizational culture is a very complex and extensive issue, which is influenced not only by the culture of the individuals who work in the organizations, but also by the culture of the country where the organizations are settled. This article has also tried to emphasize the matter of organizational culture itself and its relation to the success of the Knowledge management. The organizational learning was presented as an alternative for easing the culture and facilitate the processes of knowledge management.